Migration, displacement and social integration - Nicholas Van Hear (United Nations Research Institute for Social Development (UNRISD), 1994)
From being a relatively peripheral concern, migration has since the late 1980s moved swiftly up the policy-making agenda to become an issue of public debate. International conferences on migration issues have proliferated, and newspapers and magazines carry lengthy features on migrants, refugees and asylum-seekers almost daily. At the same time, xenophobia and racism have become prominent once again. Migration, however, has long been a feature of the world stage, and during many periods it has been seen as a beneficial phenomenon. Moreover, despite the current anxieties, many still think that migration makes a positive contribution. This paper places human migration and displacement within the context of globalization, economic and political restructuring, and social integration. It demonstrates the ambiguous impact of migration on social integration: the paradox of today's migration is that it is or may be both disintegrative and integrative, both in migrants' countries of origin and destination.
Keywords: 330